Kajian Tingkat Pelayanan Fasilitas Sosial Berdasarkan Persepsi Masyarakat Di Perkotaan Subang - Meyliana Lisanti; Reza Martani Surdia (Jurnal Planologi Unpas, 2016)
The development of an urban area should be followed by the availability of a complete and can serve the needs of local people, so it needs to be the availability of social services and facilities. It is equally the case in Subang Urban requiring the study of social fasiitas service levels. The purpose of this study was to identify and analyze service levels based on the public perception of social facilities in Subang Urban. The method used in the preparation of this report are quantitative and qualitative methods, where the method of calculating the quantitative analysis of the level of service based Infrastructure (Decree of the Minister of Settlement and Infrastructure No. 534 / KPTS / M / 2001 and Standards of the Ministry of Education and Culture) and qualitative analysis methods to see the analysis results of the public perception (questionnaire). Results from this study is that it can be seen villages where and what facilities they need to increase its services, so it needs to increase in order to increase and equity of social facilities so they can be melayanai population and the availability of social amenities which there can be affordable by the population, whereas for social facilities the critical condition can be repaired for reuse so that the level of service social amenities in urban Subang better.